The Knowledge of NAPZA Effects Toward Students’ Oral and Dental Health of Gender-Based - Ristya Widi Endah Yani (Humanistic Network for Science and Technology (HNST), 2017)
Background: Recently, NAPZA abuse has commonly happened for those who do not have understanding about its effect, especially teenagers, both females and males. However, it could bring some negative effects such as social–function disturbances, occupational as well as dental and oral health problem, which causes the increasing score of dental plaque, dental caries and periodontal. Purpose: This study is aimed to investigate KKN (Kuliah Kerja Nyata or Student Study Service) students’ knowledge about NAPZA effect toward their dental and oral health behavior based on gender differences. Methods: Analytic observational methodwith cross sectional approach was done (19 of March, 2017) among the KKN students in Glingseran village, Wringin District, Bondowoso,Indonesia and carried out 45 respondents. Besides, the variable is the understanding of NAPZA effect toward students’ dental and oral health, both females and males (assessed by answering questionnaire). The data provided are table and figures analyzed by using Mann Whitney Test either. Results: It was found that the mean score of NAPZA effect knowledge toward dental and oral health among the students,either females (84.7) or males (80.9), is categorized as very good. Moreover, there is no differences (p= 0.558) regarding to the understanding of NAPZA effect of KKN students’ dental and oral health, bothmales and females. Conclusion: There is no difference on knowledge of drugs’ effect on oral’s health between male and female KKN students. Keywords: Knowledge, NAPZA, Dental and oral health, KKN students